2019
DOI: 10.2166/ws.2019.111
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater contamination characterization using multivariate statistical analysis and geostatistical method

Abstract: The aim of the present study is to identify sources of groundwater contamination in Rupnagar district, Punjab, using an integrated approach of exploratory factor analysis (EFA) and ordinary kriging (OK). For this, a 13 physico-chemical parameter data set at 14 sampling locations for a period of over 25 years was assessed. The correlation was statistically examined amongst parameters. A five-factor model is proposed which explains over 89.11% of total groundwater quality variation. Three semi-variogram models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…From the hydrogeological point of view, the area is primarily filled with quaternary sediments, mainly of fluvial nature. The main geological units in the region include newer alluvium, older alluvium, upper and lower shiwalik (Figure ) (Chaudhry et al, 2019). The oldest alluvium known as the Ludhiana formation (the mid to late Pleistocene) consists of materials such as clay, fine sand, gravel and silt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the hydrogeological point of view, the area is primarily filled with quaternary sediments, mainly of fluvial nature. The main geological units in the region include newer alluvium, older alluvium, upper and lower shiwalik (Figure ) (Chaudhry et al, 2019). The oldest alluvium known as the Ludhiana formation (the mid to late Pleistocene) consists of materials such as clay, fine sand, gravel and silt.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, FL acts as an important method for transmitting outcomes in a very clear language format (also known as linguistic variables) to the public and beneficiaries. Several studies have used FL in assessing the quality of groundwater (Abbasnia et al, 2018; Chaudhry et al, 2019; Liu et al, 2021) and have suggested addressing complex water quality issues. All these studies implemented the FL GIS‐based GQI (FGQI) technique using point‐based short‐term data (Dahiya et al, 2007; Selvaraj et al, 2020; Vadiati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Given that no other natural source of fluoride exists in the study region, various anthropogenic activities also contribute to increasing the fluoride concentration in the region (i.e. brick kilns, industrial and domestic wastewater discharge, increase in the use of fertilizers, mining activities, and extreme irrigation practices) (Chaudhry et al 2019a). The broad gap between the groundwater residence time and the charging area alongside Ca 2+ insufficient groundwater level is responsible for Na + -HCO3level groundwater in the region.…”
Section: Spatial Distribution Of Fluoridementioning
confidence: 98%
“…Singh et al (2011) reported a significant range of fluoride (0.05-0.65 mg/L) in the region. Chaudhry et al (2019a) reported that fluoride in the region is due to an increase in anthropogenic activities and geogenic processes such as weathering and the breakdown of rocks. In the study conducted by the Geological Survey of India (GSI) for the northern region (GSI 2017), metamorphic and igneous rocks (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the increasing number of physical and chemical variables of groundwater, a wide variety of statistical methods are now used for accurate analysis and interpretation of data (Subyani & Al Ahmadi 2010). Multivariate statistical analysis methods have been used frequently in fields such as soil and water resources in the last years (Masoud et al 2018;Chaudhry et al 2019;Dash & Kalamdhad 2021). Cluster analysis (CA), factor analysis (FA), principal components analysis (PCA), discriminant analysis (DA) and several other multivariate statistical analyses are widely used to present spatial variations in groundwater quality and to determine impact factors (Ma et al 2014).…”
Section: Introductionmentioning
confidence: 99%